Changes in insight throughout the natural four-year course of obsessive-compulsive disorder and its association with OCD severity and quality of life - Wolf, Nadja; du Mortier, Johanna A. M.; van Oppen, Patricia; Hoogendoorn, Adriaan W.; van Balkom, Anton J. L. M.; Visser, Henny A. D. (Frontiers in Psychiatry, 2023)
Objective: Patients with obsessive-compulsive disorder (OCD) and poor insight show higher symptom severity, lower quality of life (QoL) , and a reduced treatment response compared to patients with good insight. Little is known about changes in insight. This study explored the course of insight and its association with OCD severity and QoL among 253 patients with OCD participating in the prospective naturalistic Netherlands Obsessive Compulsive Disorder Association (NOCDA) Study. Results: In 70% of the participants with available insight data, the level of insight changed during the four-year course. Insight was most variable in participants with poor insight. Improvement of insight scores was statistically significantly associated with improvement of Y-BOCS scores (r=0.19), but not with changes in QoL scores. Change in insight in the first two years was not statistically significantly predictive of OCD severity or QoL at four-year follow-up. Conclusions: These findings suggest that patients’ levels of insight may change during the natural four-year course of OCD and that improvement in the level of insight have a positive association with improvement in OCD severity.